A STUDY ON INSTRUCTIONAL SUPERVISION BY PRINCIPALS IN TYPE 1C AND TYPE 2 SCHOOLS IN SRI LANKA - Kumari, H. M. Lalitha (PEOPLE: International Journal of Social Sciences, 2019)
The main purpose of this study was to examine how principals’ engage in instructional supervision in Type 1C and Type 2 school in Sri Lanka. Three research questions were used to guide the study to a rational conclusion. Mixed Method was adopted in the study in order to triangulate data. Both questionnaire and semi structured interview schedules were used to obtain relevant data from 150 teachers, 10 principals and 10 sectional heads in 10 selected Type 1C and Type 2 schools using the simple random sampling techniques. Tables, percentages and graphs were used to analyze quantitative data and the qualitative data was analyzed by using thematic analysis and answer the research questions. The findings revealed that all the principals in the type 1C and Type 2 schools have positive perception about the role of instructional supervision and have formed an instructional supervisory team including the principal. However, the study revealed that the majority of principals in the type 1C and Type 2 schools do not engage in role of instructional supervision due to the major challenge of having engage in general administration roles than the instructional roles. The study further revealed that the existing internal supervisory team engage in instructional supervision role rarely and do not conduct post observational discussions which facilitate teachers to identify their strength and the areas that need further improvement. It is, therefore, recommended that, the principals need to carry out an adequate instructional supervision of teachers so as to improve their teaching skills and professional development.